Leukemia Blast Crisis: A Simulation Case for Residents - Lauren Conlon; Elizabeth Gillenwater (Association of American Medical Colleges, 2016)
Abstract Introduction Oncologic emergencies are life-threatening and often require advanced team-management skills as well as a mastery of disease processes and therapeutic interventions. Simulation of an oncologic emergency case is a useful way to experience, reflect on, and practice these skills. This case involving a simulated patient in blast crisis was created as part of our Emergency Medicine (EM) Resident Simulation Curriculum at the Perelman School of Medicine at the University of Pennsylvania. Methods This case is based on an actual patient seen in our emergency department and highlights specific teaching points and potential pitfalls in treatment algorithms. It details a 40-year-old female with history of acute myeloid leukemia presenting with fatigue for 2 days, tachycardia, and labored breathing. The patient develops worsening respiratory distress if not intervened upon and progresses to pulseless electrical activity arrest. Lab work is notable for markedly elevated white blood cell count and acidosis. A SimMan or SimMan3G is required for the simulation. The associated debriefing materials are Included in this educational resource. Evaluation of learner performance is mapped to the EM Milestones. Results Eighteen of the 20 (90%) EM residents that participated in this simulation, responded to the Likert-scale postsession survey. Of those who responded, 83% agreed or strongly agreed that the case was realistic and 89% agreed or strongly agreed that the case was useful. Discussion The simulation venue offers a unique opportunity to address team dynamics as well as provide a forum for didactic learning as it is often difficult to debrief a critical case while working in real-time patient care settings.